THE INFLUENCE OF ELECTRONIC WORD OF MOUTH ON ONLINE PURCHASE DECISIONS FOR MONITOR PRODUCTS: Survey to GTID Discord Forum Members - Firdaus, Ivan Rizqi; Huda, Anam Miftakhul (The Commercium, 2024)
The background to this research began with the existence of an online discussion place through an application called Discord, where the online discussion place was formed by GTID with a total of 46,884 members. In the GTID Discord, information is exchanged about electronic products, one of which is monitors, where the information is provided by members who need information about certain monitor products. This research aims to find out how much the Discord GTID discussion forum can influence online purchasing decisions for monitor products.The research uses Stimulus Response theory, with a quantitative approach. Sample determination uses purposive sampling techniques with the criteria of GTID Discord members, wanting to buy monitors online, having interacted in searching for information about monitors. Data collection was carried out using a survey method, namely by distributing questionnaires via Google Form, the analysis used was a simple linear regression analysis method which was processed using the SPSS application with hypothesis testing, namely the t test with t-count calculations.Based on the presentation of the results of the hypothesis test which has been carried out using a simple linear regression test method, it can be seen that the resulting R square value is 0.350, which means 35% of online, by obtaining the regression equation Y 17.278 + 0.874X with the results of the t test where .